2008
DOI: 10.1007/s11707-008-0014-0
|View full text |Cite
|
Sign up to set email alerts
|

Chronology of the shell bar section and a discussion on the ages of the Late Pleistocene lacustrine deposits in the paleolake Qarhan, Qaidam basin

Abstract: Shell bar, composed of abundant fossil shells of Corbicula fluminea mü ller and Corbicula largillierti philippi and located at the southeastern end (36u309N, 96u129E) of the paleolake Qarhan, is one of the most prominent features in the Qaidam basin. It is the highest site where such species of fossil shells have been found in the Late Pleistocene age. A 2.6-m-thick fresh profile was manually excavated to determine the formation ages and the scope of the high paleolake levels. Accelerator mass spectrometry (AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The Shell Bar, which is composed of fossil shells (Corbicula) and has the appearance of a bar, is located at the southeastern end of the Qarhan paleolake (36°30'N, 96°12'E) in the Qaidam Basin. Previous works have shown that this section was formed between 39.7 and 17.5 14 C ka BP and represents the highest paleolake development period since the late Pleistocene era (Zhang et al, 2008a).…”
Section: Study Area and Samplingmentioning
confidence: 85%
“…The Shell Bar, which is composed of fossil shells (Corbicula) and has the appearance of a bar, is located at the southeastern end of the Qarhan paleolake (36°30'N, 96°12'E) in the Qaidam Basin. Previous works have shown that this section was formed between 39.7 and 17.5 14 C ka BP and represents the highest paleolake development period since the late Pleistocene era (Zhang et al, 2008a).…”
Section: Study Area and Samplingmentioning
confidence: 85%
“…We assume a warm climate with high precipitation during these two intervals, which was similar to, or slightly greater than, that of the Holocene maximum, consistent with recent publications from sites in (semi‐) arid western China (Fang et al ., 1999; Ning et al ., 2008; Jiang et al ., 2011; Cheng et al ., 2012; Long et al ., 2012b; Wei et al ., 2015) and central Asia (Cheng et al ., 2016). This is different from the results of previous studies on the Shell‐Bar‐derived lake level changes, which documented a wettest condition during the late MIS3 (Chen and Bowler, 1986; Zhang et al ., 2008). Warm climate background was recorded by the δ 18 O curve of the Guliya ice core from the west Kunlun Mountains on the northern margin of the Tibetan Plateau (Thompson, 1997) during the early MIS3, when the NHSI reach its maximum (Laskar et al ., 2004), superimposing on the (multi‐) millennial events.…”
Section: Discussionmentioning
confidence: 99%
“…3) that has often been used as evidence in support of the lake-based GLP reconstructions. Various 14 C dates have suggested the feature formed *48-28 ka BP (Chen and Bowler 1986;Bowler et al 1986;Chen et al 1990) or *40-18 ka BP (Zhang et al 2007(Zhang et al , 2008a. Initial geomorphic interpretations of the feature Bowler 1985, 1986;Chen et al 1990) suggested that the Shell Bar was part of a paleoshoreline formed during a high stand of a mega-lake that covered much of the Qaidam Basin.…”
Section: Introductionmentioning
confidence: 99%